2020
DOI: 10.2967/jnumed.119.239558
|View full text |Cite
|
Sign up to set email alerts
|

The Role of 89Zr-Immuno-PET in Navigating and Derisking the Development of Biopharmaceuticals

Abstract: The identification of molecular drivers of disease and the compelling rise of biotherapeutics have impacted clinical care but have also come with challenges. Such therapeutics include peptides, monoclonal antibodies, antibody fragments and nontraditional binding scaffolds, activatable antibodies, bispecific antibodies, immunocytokines, antibody-drug conjugates, enzymes, polynucleotides, and therapeutic cells, as well as alternative drug carriers such as nanoparticles. Drug development is expensive, attrition r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 58 publications
(75 reference statements)
1
46
0
Order By: Relevance
“…As a result, 67 Ga was once widely used in nuclear medicine, but it is not an ideal radionuclide for diagnostic imaging. The reason is that its γ photons abundance, suitable for imaging, is quite low compared to 111 In, i.e., to achieve the same γ photon detection efficiency, the amount of 67 Ga used must be three times that of 111 In.…”
Section: Gamentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, 67 Ga was once widely used in nuclear medicine, but it is not an ideal radionuclide for diagnostic imaging. The reason is that its γ photons abundance, suitable for imaging, is quite low compared to 111 In, i.e., to achieve the same γ photon detection efficiency, the amount of 67 Ga used must be three times that of 111 In.…”
Section: Gamentioning
confidence: 99%
“…Radiopharmaceuticals can be small molecule compounds or radiolabeled biological macromolecules, such as antibodies. Zevalin ( 111 In-and 90 Y-ibritumomab tiuxetan) is a monoclonal antibody drug that has been approved by the FDA for the diagnosis and treatment of non-Hodgkin's lymphoma (NHL) [3]. Because monoclonal antibodies have high specificity for certain antigens, they can be used as therapeutic drugs for tumors and other diseases, such as the serious COVID-19 epidemic (coronavirus disease 2019).…”
Section: Radiopharmaceuticals Based On Zr-89mentioning
confidence: 99%
“…In a recent review, Van Dongen et al illustrated why 89 Zr-immuno-PET has become an important tool for the in vivo characterization of novel biological drugs and their targets (1). A technical State of the Art summarized PET quantification of 89 Zr-tracer uptake, stressing that total-tissue uptake results from a target-specific and a non-specific contribution.…”
Section: -8521 To the Editormentioning
confidence: 99%
“…This description is fully in line with a previous study co-authored by van Dongen, using Patlak analysis in normal tissues (kidneyliver-lung-spleen) without known target expression for four 89 Zr-labeled mAbs, respectively (2). Van Dongen et al thus suggested that future quantitative 89 Zr-immuno-PET studies should consider multiple-time-point acquisitions to assess non-specific-uptake versus time, with at least three late time-points, and that sophisticated modelling strategies should be developed (1,2).…”
Section: -8521 To the Editormentioning
confidence: 99%
See 1 more Smart Citation